The Implementation of the Jigsaw Learning Model to Improve Students Learning Outcomes in the Subject of Akidah Akhlak for Grade VI at MI PSM Gedoro Ngawi - Utami Nur Ajizah, Ratna; Anwar, saiful; Saskiya, Anggun; Nur Alipah, Dewi; Halima, Miftahul (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2023)
With the development of science and technology, education in Indonesia continues to progress, and globalization is advancing. The goals of education cannot be achieved without a learning process within an educational institution. To attain perfect learning objectives, teachers need to innovate in their teaching methods. Jigsaw is a structured group work strategy based on cooperation and responsibility. In this research, the researcher employed the Classroom Action Research (CAR) method. This strategy is appealing when the material to be studied can be divided into several parts and does not require a specific sequence of delivery. Based on the results and discussion of the research, the researcher concludes that the use of the jigsaw learning model is capable of improving the learning outcomes of sixth-grade students in the subject of Akidah Akhlak at MI PSM Gedoro Ngawi. According to the data achieved, the percentage increase in learning outcomes in the first cycle was 35%, while in the second cycle, it increased to 83%. Additionally, the level of student engagement also increased, with 9 active students in the first cycle rising to 19 in the second cycle. With the jigsaw learning model, students can understand and actively participate in learning. The classroom appears more lively and enthusiastic as students engage in discussions about the sub-materials provided by the teacher.